Organizational learning and strategic capability: A study of telecommunications firms in Port Harcourt - Obiageri Felicitas Onwuegbule; Benedict Chima Onuoha (Northern Negros State College of Science and Technology (NONESCOST), 2022)
This research investigated the relationship between organizational learning and strategic capability of telecommunication firms in Nigeria using cross-sectional research survey. Five telecommunication firms were surveyed with simple random sampling. Two hundred and two participants represented the accessible population. Sample size of one hundred and thirty-four was determined from the accessible population. Pearson Product Moment Correlation Coefficient (rs) was employed to analyze the research hypotheses with the aid of IBM SPSS 22.0. Copies of questionnaire was to collect data. One hundred and thirty-four copies were administered to the participants while one hundred and twenty-three copies were filled correctly and found valid for analysis. The study found that organizational learning has significant positive correlation with strategic capability of telecommunication firms. Specifically, it was found that exploitative learning has significant positive relationship with technological capability; explorative learning has significant positive relationship with marketing capability. One of the implications of this study is that managers of telecommunication firms should ensure that learning is embedded in their organizational culture so that whenever there is external turbulences, they would be able to learn from the previous experiences and remain relevant in their businesses.